Genotypic characterization of non-O157 Shiga toxin-producing Escherichia coli in beef abattoirs of Argentina - Masana, Marcelo (2011)
Fil: Masana, Marcelo O. Instituto Tecnología de Alimentos. Centro de Investigación de Agroindustria. Instituto Nacional de Tecnología Agropecuaria; Argentina.